Management of Sri Gethuk Waterfall Attractions - Anthon, Tino Asprilla; Triputro, R Widodo; Suharyanto, Suharyanto (Interdisciplinary Social Studies, 2021)
The management of Sri Gethuk Waterfall which is managed by the Tourism Village Business Unit under the Village-Owned Enterprise "Sejahtera" Bleberan Village is quite successful because it has an impact on the number of visitors which increased significantly from 2011-2015 impacting on Village Original Income (PADesa) of Bleberan tourism village. This study aims to unveil the management of Sri Gethuk Waterfall tourism object. This type of research is qualitative descriptive, which means exposure of situations and events, describing in detail and in depth the conditions that actually occur according to what is in the field which in this case is about the management activities of Village-Owned Enterprise Sejahtera in Bleberan Village. Management of Sri Gethuk Waterfall Tourism Object by Village-Owned Enterprise Sejahtera starting from the bottom up planning stage of development . Village-Owned Enterprise should continue to encourage changes in terms of planning, especially the management of business units also needs good management. Push management system through one door. This will make access easier and speed up the service.